ANALISIS KUALITAS LAYANAN WEBSITE BTKP-DIY MENGGUNAKAN METODE WEBQUAL 4.0 - Putra, Zahreza Fajar Setiara; Sholeh, Mohammad; Widyastuti, Naniek (Jurnal Jarkom, 2014)
ABSTRACTWebQual method is one method or technique of measuring the quality of a website based on the perception of the end user. This method is the development of a method developed by Parasuraman SERVQUAL, which is widely used prior to the measurement of service quality. Research on the WebQual instrument developed by the method of Quality Function Development (QFD). WebQual been developed since 1998 and has undergone several iterations in the preparation of the dimensions and the question grains. Research Barnes and Vidgen (2003) who used WebQual 4.0 to measure the quality of a website maintained by the OECD (Organization for Economic Cooperation and Development). In the process of analysis of the sample used tranches of 100 respondents consisting of principals, teachers and students in elementary and junior high schools in the region. The next stage is data analysis which consists of test validity, reliability testing and assessment with a Likert scale. In the validity test using Pearsons formula Bevariate while reliability test using Cronbachs alpha formula. In the assessment using a Likert scale used 4 assessment intervals, ie Very Satisfied, Satisfied, Satisfied and Dissatisfied Less.Keywords: WebQual, validity, reliability, Likert Scale.